DISTRIBUSI PASAR LUAR NEGERI DAN LOGISTIK GLOBAL - Fernanda Putri; Suhairi; Vira Audini; Abdullah Haris Lubis (STIE Mahardhika, 2023)
Distribution is one of the most useful trading techniques, because distribution is used to describe and distribute the flow of goods or services from producers to consumers on a predetermined budget and time. By distributing goods or services to foreign markets will make marketing wider and reach large-scale trade. Logistics is used to carry out goods sent from one place to another, global logistics has several types, namely logistics in foreign markets, multi-market logistics, dynamic environments and flexible responses. Meanwhile, international logistics is sending or carrying out goods by sending them between countries with other countries with the facilities and technology they have to carry out shipments. The conclusion that we can draw is that the distribution of foreign markets greatly influences the increase in demand for goods or services by using logistics to carry out this distribution. This writing uses the method of literature study, using central data collection methods, reading, recording and processing research materials